PUBLIC INSTITUTIONS AS DRIVERS FOR ACTIVATING COOPERATION OF TERRITORIAL COMMUNITIES - HLAZOV, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The study revealed the relevance of research and development of methodological and applied principles of the toolkit of public institutes in the context of cooperation between territorial communities in Ukraine. The purpose of the article is to improve the methodological and practical principles of using the tool of public institutions in Ukraine as a driver for the development of cooperation between territorial communities. The prospects for the activity of public institutions of Ukraine as drivers of cooperation between territorial communities have been determined. Public institutions are considered in a broad sense - as subjects of local self-government (bodies of self-organization of the population, associations of local self-government bodies, local public organizations) and as separate subjects of interaction with communities. A systematic presentation of the organizational and legal foundations of cooperation between territorial communities and public institutions in Ukraine allowed to confirm their limited functionality, which, as a rule, involves educational activities, mediation and mentoring of community participation in international programs. It was also confirmed that there are no stable practices of partnership between civil society institutions and local self-government bodies in Ukraine. Taking into account the limited experience of territorial communities in cooperation, special attention is paid to the need to implement projects of public institutions for the purpose of supporting the territorial community in gaining the first experience of cooperation and acquiring a grant history. Other recommendations include the implementation of projects for communities focused on socio-demographic potential, ecologically oriented projects, projects focused on increasing the financial capacity of communities with subsequent involvement of own funds in project activities. The task of state authorities is to support the development of regional partner networks through popularization of their experience, state guarantees for participation in valuable international projects. Communities themselves should stimulate the creation of local public organizations, public councils under local self-government bodies, implement the principle of "community foundation" to support the global philanthropic movement.